2016
DOI: 10.1111/cccr.12139
|View full text |Cite
|
Sign up to set email alerts
|

The Gulabi Gang, Violence, and the Articulation of Counterpublicity

Abstract: This essay analyzes the resistive tactics of the Gulabi Gang in rural India between approximately 2006 and 2013, asserting the Gulabi Gang as a counterpublic that used violence to negotiate and achieve its counterpublicity. The Gulabi Gang represents a nodal point in a rich and complex history of resistance against gender-and caste-related violence in India. Through this analysis, I contend the group implicitly challenges the prearranged distinction between violence and legitimacy, which undergirds popular dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Gender socialization in India is a complex phenomenon (Desai & Temsah, 2014). While many families are matriarchal in nature (Cybil, 2016), women in some communities learn to combat oppression in creative ways (Richards, 2016). Indeed, Indian women are not always the victims of oppression (Desai & Temsah, 2014).…”
Section: Gender Socialization In Indiamentioning
confidence: 99%
“…Gender socialization in India is a complex phenomenon (Desai & Temsah, 2014). While many families are matriarchal in nature (Cybil, 2016), women in some communities learn to combat oppression in creative ways (Richards, 2016). Indeed, Indian women are not always the victims of oppression (Desai & Temsah, 2014).…”
Section: Gender Socialization In Indiamentioning
confidence: 99%
“…Yet where such institutions remain unmovable and intransigent in face of persuasion, disobedience may be warranted as a form of passive resistance against injustice. Democratic regimes, too, could be obstinate in face of movements seeking empowerment and rectificatory justice – consider, for instance, the violence championed by Malcolm X and adopted by forces such as the Black Panther Party against white-supremacist groups and the political disenfranchisement confronting African-Americans in 20 th century America (Shelby, 2005); or alternatively, the violence embraced by vigilante groups such as the Gulabi Gang (Richards, 2016, pp. 558-76) against sexual predators in India.…”
Section: Why Conscientious Disobedience Is Normatively Distinctmentioning
confidence: 99%
“…They showed that multiple or contradictory interpretations and polyvalence of language and expressions not only bridged the popular and the political but also opened up novel avenues for citizen participation and performativity. For example, one article critiqued the dominant practice of land-grabbing, which caused large-scale displacement of rural populations (Pal & Dutta, 2013), whereas another article documented a women-initiated collective resistance, namely Gulabi Gang, against gender and caste related violence in India (Richards, 2016). In terms of organizing for social movement, scholars explored both online and offline avenues for activism.…”
Section: Language and Verbal Communicationmentioning
confidence: 99%